Cytokine Gene Expression in Human LPS- and IFNγ-stimulated Mononuclear Cells Is Inhibited by Heparin - Attanasio, Monica; Gori, Anna Maria; Giusti, Betti; Pepe, Guglielmina; Comeglio, Paolo; Brunelli, Tamara; Prisco, Domenico; Abbate, Rosanna; Gensini, Gian Franco; Serneri, Gian Gastone Neri (Thrombosis and Haemostasis, 1998)
In addition to its well-understood anticoagulant activity, heparin is known to modulate a variety of biological functions including immuno-logic responses. In order to investigate whether heparin influences the humoral immunity by interacting with cellular elements and affecting gene expression in blood circulating cells, we studied the effect of heparin on IL-1β, IL-6 and TNFα mRNAs in human lipopolysaccharide(LPS)- or interferon-γ(IFNγ)-stimulated mononuclear cells. The study of mRNA was carried out by an initial PCR screening followed by a Northern blot quantitative analysis. Heparin (0.5 U/ml) turned out to inhibit all three cytokine gene expressions. The mRNA decrease was 37 ± 6% for IL-1 β, 53 ± 3% for IL-6 and 47 ± 4% for TNF α with LPS stimulus. No differences could be observed in the inhibitory effect of heparin on IFNγ-stimulated cells. This effect of heparin was confirmed in a subset of experiments performed on purified monocytes. These results suggest an important immunosuppressive effect of heparin on cell-mediated immune responses.